Asymmetric Transmission in the Planar Chiral Nanostructure Induced by Electric and Magnetic Resonance at the Same Wavelength. Issue 7 (2nd April 2019) - Bai, Yu; Wang, Tiankun; Ullah, Hamad; Qu, Yu; Abudukelimu, Abuduwaili; Zhang, Zhongyue
Abstract: Asymmetric transmission (AT) reflects the conversion efficiency of a chiral nanostructure for circularly polarized light and is widely used in polarization and optoelectronic devices. In this study, a new mechanism is proposed to generate AT when a planar chiral nanostructure is illuminated under left‐handed circularly polarized (LCP) and right‐handed circularly polarized (RCP) light illumination. The new mechanism can be achieved by breaking the symmetry of the designed planar chiral nanostructure which give rise to a new transmittance peak and dip at a particular wavelength under RCP and LCP light illumination, respectively. The proposed new mechanism is also capable of actively tuning the generated resonant modes. Besides this, when graphene strips are added to the designed planar chiral nanostructure, similar results are obtained as that from breaking the symmetry of the planar chiral nanostructure. In this case, the generated AT could also be actively tuned by varying the Fermi energies of graphene strips. Abstract : An S‐shaped nanostructure is proposed to generate asymmetric transmission (AT) signal under circularly polarized light illumination. A new mode, which is the resonance peak‐dip mode, is produced by breaking the symmetry of the designed structure under right‐ and left‐handed circularly polarized light illumination. The AT signal can be actively tuned by varying the Femi energy.